(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This research will reveal how the empowerment of village apparatus resource in Kuyanga is caused by not yet optimal service given by village government apparatus. Research method applied in this research is qualitative research method intend to get a clear picture about Empowerment of Resource of Kuyanga Village Apparatus. Sources of data or informants in this study were taken from various elements covered as apparatus of Kuyanga Village with data collection techniques used Interview, Observation and Documentation Based on research empowerment of government apparatus of Kuyanga Village have good seen from independence in solving existing problems in society. Village officials are quick to respond and have good responsibilitas to address the circumstances surrounding. Kuyanga village officials were agile and proactive enough to respond to complaints Keywords: Empowerment, Apparatus Resources, and Village